State of Philippine competitiveness and innovation - Uriarte, Filemon A. (ERDT Congress)
The paper describes and assesses the state of Philippine competitiveness and innovation, first, by reviewing the results and observations of relevant studies, and second, by studying the historical and comparative trends of Philippine competitiveness and innovation as measured by authoritive international studies and reports. It also covers briefly the country's response to the challenge of enhancing national competitiveness and promoting innovation.